Framing Messages to Deal With the COVID-19 Crisis: The Role of Loss/Gain Frames and Content - Gantiva, Carlos; Jiménez-Leal, William; Urriago-Rayo, Joan (Frontiers in Psychology, 2021)
The goal of this study was to test the role of message framing for effective communication of self- care behaviors in the context of the COVID-19 pandemic, contrasting health and economic-focused messages. We presented 319 participants with an unforced choice task where they had to select the message that they believed was more effective to increase intentions toward self-care behaviors, motivate self-care behaviors in others, increase perceived risk and enhance perceived message strength. Results showed that gain-frame health messages increased intention to adopt self-care behaviors and were judged to be stronger. Loss-framed health messages increased risk perception. When judging effectiveness for others, participants believed other people would be more sensitive to messages with an economic focus. These results can be used by governments to guide communication for the prevention of COVID-19 contagion in the media and social networks, where time and space for communicating information are limited.